Deliberative Bureaucracy: Reconciling Democracy's Trade-off Between Inclusion and Economy. (August 2018) - Boswell, John; Corbett, Jack
Deliberative democrats have long considered the trade-off between norms of inclusion and efficiency. The latest attempt at reconciliation is the deliberative systems model, which situates and links individual sites of deliberation in their macro context. Yet, critics argue that this move to scale up leaves inclusive practices of citizen deliberation vulnerable. Here, we seek to mitigate these concerns via an unlikely source: bureaucracy. Drawing on the notion of policy feedback, with its attendant focus on how policies (re)make democratic politics, we envision a deliberative bureaucracy where implementation and service delivery are imbued with norms of justification, publicity and, most radically, inclusion. Looking at promising contemporary governance practices, we argue that a deliberative bureaucracy, with the rich public encounters it might foster, can reconcile the desire to scale up deliberative democracy to whole systems with the desire to hold on to the benefits of scaled-down citizen deliberation.